A Nonlinear Macro-Model for the Analysis of Monotonic and Cyclic Behaviour of Exterior RC Beam-Column Joints - Grande, Ernesto; Imbimbo, Maura; Napoli, Annalisa; Nitiffi, Riccardo; Realfonzo, Roberto (Frontiers in Materials, 2021)
The study presents a numerical investigation on exterior reinforced concrete (RC) beam-column joints under seismic actions based on a macro-modelling approach proposed by the authors in a recent paper. The followed approach makes use of the well-known “scissors model” where two nonlinear rotational springs arranged in series were introduced to schematize the shear behavior of the joint panel and, moreover, the possible occurrence of the debonding of longitudinal steel rebars at the beam-joint interface. In this paper, the scissor model is employed in the context of a novel predictive approach with the twofold objective to: a) develop a new model for the estimate of the maximum shear strength of RC joints by performing a multivariate linear regression analysis on a set of experimental tests and, b) define a new multilinear backbone joint shear stress-strain law to be assigned to one of the mentioned springs. In particular, the identification of the shear strain parameters is obtained by performing a sensitivity analysis in which a number of monotonic load-drift numerical curves are derived by varying the strain values in ranges opportunely a-priori defined and compared with the experimental ones to investigate their accuracy. Finally, cyclic analyses on RC joints collected in the experimental database are carried out by considering the backbone joint shear stress-strain law identified in the calibration process. The analyses are performed by using the nonlinear open-source finite element platform, OpenSees, in which the “pinching4” uniaxial material model, available in the software library, is implemented to set the parameters governing the hysteresis rules and pinching effect. To this purpose, five literature proposals suggesting the values to use for such parameters are taken into account and their assessment is presented in the paper. The obtained outcomes have allowed, on the one hand, to identify the proposal providing the best numerical simulations of the experimental results and, on the other end, to draw useful indications on how to further improve the cyclic modelling by opportunely modifying the setting of the “pinching4” material model parameters.